Stress disease of the 21st century? - Robert Chudzik; Katarzyna Jarosz; Maria Gołębiowska; Beata Gołębiowska (Kazimierz Wielki University, 2017)
The concept of stress is already 80 years old, the issue is getting better researched. Mechanisms of action better understood. We notice the difference between eustress and distress - that what is good and usefull for our body, and what is not. This topic of this research is getting more and more important - faster and faster pace of life, more and more civilization diseases. 77% of people regularly experience physical symptoms of stress, while psychologically, 73%. With such figures, the authors would like to draw attention to the importance of this issue and to what are the latest findings in this area, what else has to be done and how can we now handle it. The amount of illness that is associated with stress is enormous. Whether directly as their main cause or indirect as a factor predisposing to its occurrence. Literature provides numerous examples of immunology, cardiology or neurology. Extremaly worrying is the impact of stress during pregnancy to the adult life of an unborn child. Of course we can also find ways of treating it, whether it is pharmacological: stress or its consequences or by reducing stress. In conclusion, this is a significant condition that has a large effect on a large number of people. Worrying that even doctor and nurses who have knowledge of this subject is not devoid of the negative effects of stress. Exactly due to the specifics of work more exposed.